2020
DOI: 10.1111/xen.12643
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐phase silica‐based extraction leads to underestimation of residual DNA in decellularized tissues

Abstract: Decellularization of animal tissues is a novel route to obtain biomaterials for use in tissue engineering and organ transplantation. Successful decellularization is required as animal DNA causes inflammatory reactions and contains endogenous retroviruses, which could be transmitted to the patient. One of the criteria for successful decellularization is digestion (fragmentation) and elimination (residual quantity) of DNA from the tissue. Quantification of DNA can be done in many ways, but it has recently been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…The decellularization protocol reported in this study was proven to be effective in the removal of dsDNA: the DNA concentration was found under the threshold of 50 ng/mg dry tissue set by Crapo et al [ 51 ] as necessary to prevent inflammatory reactions caused by animal DNA and the transmission of endogenous retroviruses from animal to patient [ 88 ]. In order to increase both specificity and reproducibility of the DNA quantification, it was decided to apply both UV spectroscopy and fluorescence-based methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decellularization protocol reported in this study was proven to be effective in the removal of dsDNA: the DNA concentration was found under the threshold of 50 ng/mg dry tissue set by Crapo et al [ 51 ] as necessary to prevent inflammatory reactions caused by animal DNA and the transmission of endogenous retroviruses from animal to patient [ 88 ]. In order to increase both specificity and reproducibility of the DNA quantification, it was decided to apply both UV spectroscopy and fluorescence-based methods.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the relationship between residual DNA amount, fragment length, and immunological reactions following xenotransplantation has yet to be clearly defined, as the biological consequences of residual nuclear material or cytoplasmic debris within the scaffold are still unclear. There are no reports showing a direct cause–effect relation between such cellular remnants and an adverse host response to date [ 65 , 88 ]. Even though the U.S. Federal Drug Administration does not set limits for DNA in biologic scaffolds, more systematic studies are needed in order to determine a more specific threshold in terms of acceptable DNA residues.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular DNA has been implied in the severity of inflammation, 23 25 but the amounts found in healthy individuals’ plasma vary greatly depending on the quantification method and lie either below or above the published limit for successful decellularization. 49 As such, this proposed limit may not reflect a universally applicable goal, 38 especially considering the immunoprotected state of the NP within the avascular IVD. 50 Compared to the previously published protocols, we achieved a similar or greater reduction in DNA content when accounting for different normalization methods used (wet/dry weight).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA concentration was determined using the Qubit DNA assay (Qubit dsDNA HS assay, Thermo-Fisher Scientific, Landsmeer, The Netherlands) following the manufacturer’s instructions. DNA fragment lengths were examined on a 1% agarose gel: 250 μL of digested sample was washed thrice with ultrapure water and then concentrated to 20 μL using ultracentrifugation filters with a 30 kDa molecular weight cutoff for gel electrophoresis 38 (wash/concentration spins: 14 000 g for 10 min, recovery spin: 1000 g for 1 min). To visualize cell nuclei, we reconstituted NCM and dNCM powder to 10% w/v in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Metal-ligand complex formation is of special significance where a specific ligand can selectively coordinate with the heavy metal ions in order to extract Water 2021, 13, 3056 2 of 12 them from the complex sample matrix [3]. In solid phase extraction (SPE), research has been focused on the preparation of new adsorbent materials including polymeric materials, nano-materials, metal-organic framework, and carbonaceous materials for wastewater remediation [15][16][17][18][19][20]. Polymeric adsorbents has been considered as a promising material, since it has an advantage of column operation over nano-materials, and widely acceptable in water treatment techniques [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%